Graphene Nanoplatelets Hybrid Flame Retardant Containing Ionic Liquid and Ammonium Polyphosphate for Modified Bismaleimide Resin: Excellent Flame Retardancy, Thermal Stability, Water Resistance and Unique Dielectric Properties - Yan Wang (MDPI AG, 2021)
To achieve the requirements of modified bismaleimide resin composites in electronic industry and high energy storage devices, flame retardancy, water resistance and dielectric properties must be improved. Hence, a highly efficient multifunctional graphene nanoplatelets hybrid flame retardant is prepared by ionic liquid graphite and ammonium polyphosphate. The preparation processes of the flame retardants are simple, low energy consumption and follow the green chemical concept of 100% utilization of raw materials, compared with chemical stripping. The bismaleimide resin containing 10 wt.% of the flame retardant show good flame retardancy, resulting in the limiting oxygen index increases to above 43%, and the peak heat release rate, total heat release and total smoke release decrease by 41.8%, 47.8% and 52.3%, respectively. After soaking, mass loss percentage of the modified bismaleimide resin only decreases by 0.96%, the dielectric constant of the composite increases by 39.4%, and the dielectric loss decreases with the increase of frequency. The hybrid flame retardants show multifunctional effect in the modified bismaleimide resin, due to the physical barrier, the chemical char-formation, hydrophobicity and strong conductivity attributed to co-work of Graphene nanoplatelets, ammonium polyphosphate and ionic liquid.